2018
DOI: 10.1002/2017jc013531
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamics of the Nearshore Boundary Layer of a Large Lake (Lake Geneva)

Abstract: We examine nearshore and pelagic current variability in Lake Geneva, a large and deep lake in western Europe, using observations from several measurement locations and a three‐dimensional numerical model for the period 2014–2016. Linear internal seiche modes excited by wind forcing clearly appear as peaks in the energy spectra for measurements in offshore locations. In contrast, spectra from the nearshore data, where currents interact with the lake bed, reveal a negligible contribution of internal seiches to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 67 publications
(110 reference statements)
2
50
0
Order By: Relevance
“…As demonstrated by Cimatoribus et al (), the model realistically reproduced the stratification, mean flow, and internal seiche variability observed in the lake. As an example, in Fig.…”
Section: Methodssupporting
confidence: 59%
See 4 more Smart Citations
“…As demonstrated by Cimatoribus et al (), the model realistically reproduced the stratification, mean flow, and internal seiche variability observed in the lake. As an example, in Fig.…”
Section: Methodssupporting
confidence: 59%
“…Furthermore, it was confirmed that the results of the particle tracking were not sensitive to the choice of using flow field snapshots at 0.5 h intervals. This was also supported by the fact that the hydrodynamic model is known to have limited variability at this short time scale (Cimatoribus et al ). An important feature of the tracking method employed in this study is that it conserves the volume, i.e., the no‐flow side and bottom boundary conditions are respected by the computed trajectories, and no particles are lost from the basin.…”
Section: Methodsmentioning
confidence: 70%
See 3 more Smart Citations